ANALYSIS OF THE CREDITFINANCING DISTRIBUTION MODEL FOR SMEs AT BANK SYARIAH INDONESIA (BRANCH OFFICE PONOROGO) - Noviana Prasanti; Naahilah Hunafaa' Al Qudsy; Taufiq Ismail (I-Economics: A Research Journal on Islamic Economics)
This study aims to find out what the financing model of People's Business Credit (KUR) at Bank Syariah Indonesia KCP Ponorogo is like and find out its application to Micro, Small and Medium Enterprises Units in Ponorogo. This research uses a descriptive method of analysis using a qualitative approach. This research uses a descriptive method of analysis using a qualitative approach. This study used primary and secondary data, with observational data collection techniques, interviews, and documentation. 1) Based on the results of the study, it was concluded that 1) Sharia Microfinance Products have many products, one of which is the People's Business Credit (KUR) program. There are several models of People's Business Credit Financing (KUR) at Bank Syariah Indonesia (BSI) KCP Ponorogo such as, KUR Super Mikro, KUR Mikro, KUR Kecil. 2) In its application, Bank Syariah Indonesia (BSI) KCP Ponorogo has several requirements such as Identity Card (KTP), Family Card (KK), marriage certificate, current account, business letter, and guarantee. The Bank has an obligation to monitor what has been given to customers, because the funds must be used according to the initial agreement.